Nanomaterials and their application in Prosthetic Dentistry: A Comprehensive Literature Review - Kumar Singh, Rohit; Nallaswamy, Deepak; Rajeshkumar, Shanmugam; Varghese, Sheeja S; Sengupta, Chandan; Anandan, Jayasree (Journal of Neonatal Surgery, 2025)
The effects of nanotechnology are profoundly found in every aspect of science and development. Particularly, the field of dentistry is being influenced by nanotechnology making use of its immense potential. It is believed that nearly in the future, the advancement in the medical realm and the introduction of scientific devices that are tiny than dust mites may be one day capable of impressive medical miracles. However, the recent upsurge in the medical field, such as microscopy has given scientists new tools to understand and take advantage of these pre-existing natural phenomena when the matter is organized at the nanoscale. These Nanoparticles can be easily manipulated for surface chemistry, bonding capability when compared with bulk material and are overpowering. The application of nanotechnology in dental sciences leads to the emergence of Nanodentistry which involves the maintenance of good oral health while using different biotechnologies and Nanomaterials with enhanced physical properties and antimicrobial potential. A variety of nanostructures such as nanofibre, nanorobotics,etc., have been considered for various applications in dentistry. Nanomaterials were included in a variety of oral health care products in the field of preventive dentistry and have been exploited in the development of restorative material. Nanomaterials have improved the treatment protocol in all important fields of dentistry such as endodontics, periodontics, tissue regeneration, implants, maxillofacial prosthetics, and restorative dentistry. This review article is an attempt to provide a brief introduction and historical background regarding nanotechnology, an overarching view on Nanomaterials, and its application in the field of Prosthodontics.